Biological components of Greek lagoonal ecosystems: an overview - NICOLAIDOU, A.; REIZOPOULOU, S.; KOUTSOUBAS, D.; ORFANIDIS, S.; KEVREKIDIS, T. (Mediterranean Marine Science, 2005)
The paper summarises the available information on the main biological components – phytoplankton, zooplankton, phytobenthos, zoobenthos and fish – of Greek lagoonal ecosystems. Meiobenthos was also studied in one of the lagoons. All components show great variability both in space and time, which is attributed to the variability of environmental conditions. The most important variable influencing species distribution and diversity is the degree of communication with the sea and the nutrient load introduced through fresh water inputs. Certain new methods, which have been applied for evaluation of the ecological quality state of the lagoons, are also presented.